2022
DOI: 10.3389/fpsyg.2022.996189
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting face mask-wearing behaviors to prevent COVID-19 among Thai people: A binary logistic regression model

Abstract: ObjectivesFace mask wearing is a standard preventive measure, in addition to handwashing and physical distancing. Individuals may find that wearing a face mask protects their physical health and prevents viral transmission. However, none of the studies in Thailand identified factors associated with face mask-wearing behaviors among Thai people. Therefore, this study aims to determine factors affecting face mask-wearing behaviors to prevent COVID-19.MethodsThis research is analytical survey research. The data u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Since RSV infections are commonly identified in schools and daycare centers [ 6 , 17 ], children who attended daycare before the COVID-19 pandemic had a higher risk of upper or lower respiratory tract infections than children who stayed at home [ 18 , 19 ]. Thus, the strict public health measures for COVID-19 resulted in a decrease in the rate of respiratory infections in Thailand [ 11 ]. According to a previous study, social separation at work helped prevent the spread of respiratory infections [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since RSV infections are commonly identified in schools and daycare centers [ 6 , 17 ], children who attended daycare before the COVID-19 pandemic had a higher risk of upper or lower respiratory tract infections than children who stayed at home [ 18 , 19 ]. Thus, the strict public health measures for COVID-19 resulted in a decrease in the rate of respiratory infections in Thailand [ 11 ]. According to a previous study, social separation at work helped prevent the spread of respiratory infections [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of patients have severe symptoms, including difficulty breathing, wheezing, bronchiolitis, and pneumonia [ 8 ]. However, the outbreak of coronavirus disease 2019 (COVID-19) affected the pattern of RSV infection [ 9 , 10 ] and decreased the incidence of RSV in many regions of Thailand from 2020 to 2021 [ 11 ]. The use of broadspectrum antibiotics during the COVID-19 pandemic in Korea dropped by 14-30% due to a decrease in ARTI-related hospitalizations related to stringent public health interventions and social distancing measures [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in Thailand revealed that 97.6% wore a face mask outside the home. 14 In Italy, a study found that most individuals (72.5%) wore face masks, 56.5% used surgical masks, and 53.0% used disposable masks. 15 Based on the photoprotection impact of masks and our patients’ behavior while wearing masks during the pandemic, this could be one of the explanations for melasma improvement.…”
Section: Discussionmentioning
confidence: 99%
“…An online survey conducted in Thailand in 2021 revealed that only 43% of 1230 adults aged at least 60 years from nine provinces across the country’s five regions possessed adequate knowledge of the disease, and only 33% engaged in preventative behaviors [ 8 ]. Furthermore, a recent large survey in Thailand demonstrated that those over the age of 60 had a higher proportion of not wearing a face mask outside the home in comparison with those aged 20 to 49 years [ 9 ]; thus, more attention should be paid to older adults’ mask-wearing behaviors.…”
Section: Introductionmentioning
confidence: 99%